Determinants of Export Performance in Emerging Market Economies: New Evidence from a Panel Quantile Regression Model - Erdem Bulut; Zaim Reha Yaşar (İstanbul İktisat Dergisi)
Export is a key driver of economic growth in emerging market economies, hence, studying the factors that influence export performance is a crucial and important phenomenon. With the use of a panel quantile regression model and annual data, we evaluate the fundamental variables affecting exports in the Brazil, Russia, India, China, and South Africa (BRICS countries), as well as Turkey, Egypt, Indonesia, and Colombia, between 1980 and 2020. Export is the model’s dependent variable, while the nominal exchange rate, foreign direct investments, inflation rate, and the economic growth rate based on Kaldor’s growth model are its independent variables. According to the findings, the nominal exchange rate has a positive impact on export at various export levels. Therefore, at both low and high levels of export, exchange rate has a greater impact on export. On the other hand, export at the lowest levels is positively impacted by economic growth and foreign direct investments. The impact of economic growth and foreign direct investments on export, however, are insignificant as export volume rises. Finally, even if there is a positive correlation between inflation and export when the export volume is high, there is no significant relationship when exports start to increase. The findings demonstrate that macroeconomic factors significantly affect export in emerging market economies.